When the prisoners ran Walpole: a true story in the movement for prison abolition - Bissonette, Jamie (South End Press, 2008)
Introduction -- Preamble: constructing punishment in Massachusetts -- Confronting the moral dilemma of Massachusetts prisons: Francis Sargent and his administration -- The new commissioner: from corrections to abolition -- The beginning: constructing corrections in Massachusetts -- Resistance, rebellion, and declaration: creating a culture of resistance -- Dynamic and determined: the National Prisoners Reform Association; Walpole chapter -- The struggle for voice and sovereignty: the NPRA negotiates power -- Stealing time: the NPRA takes over -- Soul contraband: observers witness terror and change -- Readjustment and resistance: the state police takeback -- The struggle for existence: lights out on reform? -- Those who dared: the promise of abolition -- Reflections in retrospect: lessons learned -- Endnotes -- Index -- About the author -- About SEP